Evaluasi Kolaborasi Antarnegara Dan Kebijakan Kriminal Dalam Penindakan Perdagangan Orang Sebagai Kejahatan Terorganisir Lintas Negara - Aprianti Lubis; Dwi Putri Lestariks; Wevy Efticha Sari (CV. ITTC INDONESIA, 2025)
This study evaluates international collaboration and criminal policies in combating human trafficking as a transnational organized crime. Human trafficking is a severe violation of Human Rights (HR), involving complex modus operandi such as fraud, violence, and exploitation, with women and children as primary victims. The research analyzes the characteristics of human trafficking, legal enforcement challenges in Indonesia, and the role of international cooperation through instruments like the Palermo Convention and the ASEAN Convention Against Trafficking in Persons (ACTIP). The study employs a descriptive qualitative method, with data collected through interviews, observations, and legal documents. Findings reveal that despite Indonesia’s legal framework, including Law No. 21 of 2007, implementation faces obstacles such as inter-agency coordination gaps, limited resources, and inconsistent legal interpretations. Globally, international cooperation through extradition treaties and mutual legal assistance is critical for effective enforcement. The study recommends strengthening law enforcement capacity, regulatory harmonization, and public awareness campaigns to holistically combat human trafficking.